POST-PARTUM RESUMPTION OF SEXUAL INTERCOURSE AND THE UPTAKE OF MODERN CONTRACEPTIVES AMONG WOMEN ATTENDING A TERTIARY HOSPITAL IN SOUTH WEST NIGERIA - Adenike, Olugbenga-Bello I.; Oke, Olufemi S.; Kola, Owonikoko M.; Akande, Roseline; Tolulope, Fawole; Oluwatosin, Dada; Oluwafemi, Ernest; Gabriel, Fabusuyi; Segun, Fasheyi; Abiodun, Idowu (Journal of Health, Medicine and Nursing, 2017)
Purpose: A total of 460 women, who brought their children for immunization at the Infant Welfare Clinic as well as those attending the postnatal clinic who were within 6 weeks to 6 months postpartum participated in the study. Method: This was a descriptive cross sectional study conducted among 460 women who brought their children for immunization at the Infant Welfare Clinic and those that were clients at postnatal clinic at LAUTECH teaching hospital, Ogbomoso. Results: Majority of the women interviewed were within the age range of 26-30years (185) with a mean age of 28.65 + 4.7, 208 (45.2%) had resumed sexual intercourse, among these, 80(38.9%) had sex less than 6weeks of delivery, while majority 168(61.87%) had sex within six weeks and six months of delivery. The last pregnancy was planned by 246(53.5%) of the respondents. Only 91(19.8%) had used contraception after delivery; 59(64.8%) used it between 6 weeks and 6 month while 32(35.2%) used it before 6 weeks, The mostly used method was condom, 29(31.8%), then Pills, 27(29.7%), Among the non-users, 81(17.6%) claimed they could have initiated sex earlier if they were using a contraceptive method. Significant association existed between age, occupation of mothers, marital age, husband's occupation, number of wives, order of wife and resumption of sexual activity. Conclusion: There is a need to include postpartum contraceptive counseling and sexuality as an important component of our routine antenatal and postnatal clinic.